Results of Reading Comprehension Test for Elementary School Children Who Are Addicted to Playing The Internet in The Ciputat Area, South Tangerang, Indonesia - Lestari, Mas Roro Diah Wahyu; Syofyan, Harlinda; Efendi, Yasin; Gunadi, Andi Ahmad (Education, Science, and Technology International Conference, 2024)
The purpose of this study is to find out the value of the ability to understand elementary school children who like to play mobile phones due to the impact of free internet around the South Tangerang mayor’s office. This research method uses a quantitative approach consisting of test results and interview surveys. There were 50 samples of internet-addicted children from 150 populations in the region who received free internet access in South Tangerang. Data processing uses frequency distribution. It was found that the average reading comprehension ability score in children who are addicted to the internet is 69. The highest value of reading comprehension ability is the ability to search for information, search, access and find explicit information from the discourse, namely understanding the context, the ability to find the subject of thought and the ability to answer questions where the answer is in the text. The lowest reading comprehension ability is that students have difficulty answering with their own opinions. Students who often use the internet have difficulty expressing the concept of text thoughts and concluding the content of the text.